The interactions of Canadian ethics consultants with health care managers and governing boards during times of crisis. Issue 2 (3rd April 2017) - Kaposy, Chris; Maddalena, Victor; Brunger, Fern; Pullman, Daryl; Singleton, Richard
ABSTRACT: Background : Health care organizations can be very complex, and are often the setting for crisis situations. In recent years, Canadian health care organizations have faced large-scale systemic medical errors, a nation-wide generic injectable drug shortage, iatrogenic infectious disease outbreaks, and myriad other crises. These situations often have an ethical component that ethics consultants may be able to address. Organizational leaders such as health care managers and governing boards have responsibilities to oversee and direct the response to crisis situations. This study investigates the nature and degree of involvement of Canadian ethics consultants in such situations.Methods : This qualitative study used semi-structured interviews with Canadian ethics consultants to investigate the nature of their interactions with upper-level managers and governing board members in health care organizations, particularly in times of organizational crisis. We used a purposive sampling technique to identify and recruit ethics consultants throughout Canada.Results : We found variability in the interactions between ethics consultants and upper-level managers and governing boards. Some ethics consultants we interviewed did not participate in managing organizational crisis situations. Most ethics consultants reported that they had assisted in the management of some crises and that their participation was usually initiated by managers. Some ethics consultants reported the ability to bring issues to the attention of upper-level managers and indirectly to their governing boards. The interactions between managers and ethics consultants were characterized by varying degrees of collegiality. Ethics consultants reported participating in or chairing working groups, participating in incident management teams, and developing decision-making frameworks.Conclusions : Canadian ethics consultants tend to believe that they have valuable skills to offer in the management of organizational crisis situations. Most of the ethics consultants we interviewed believed that they play an important role in this regard.